Pattern and Outcome of Pediatric Traumatic Brain Injury at Hawassa University Comprehensive Specialized Hospital, Southern Ethiopia: Observational Cross-Sectional Study - Tuji Bedry; Henok Tadele (Emergency Medicine International)
Background. Traumatic brain injury (TBI) is the most common cause of death/disability in children. The Glasgow coma scale and other parameters are used for treatment/follow-up of TBI. Childhood TBI data are scarce from sub-Saharan Africa. The study aimed to determine the pattern and predictors of the TBI outcome in Southern Ethiopia. Methods. An observational cross-sectional study was conducted from September 2017 to September 2018 at Hawassa University Hospital. Structured questionnaires were used for data collection. Significant associations were declared at a P value of <0.05. Results. There were 4,258 emergency room (ER) visits during the study period, and TBI contributed to 317 (7.4%) cases. The mean age of study subjects was 7.66 ± 3.88 years. Boys, predominantly above 5 years of age, comprise 218 (68.8%) of the study subjects with a male to female ratio of 2.2 : 1. Pedestrian road traffic accidents (RTA), 120 (37.9%), and falls, 104 (32.8%), were the commonest causes of TBI. Mild, moderate, and severe TBI were documented in 231 (72.9%), 61 (19.2%), and 25 (7.9%) of cases, respectively. Most of the TBI cases presented within 24 hrs of injury, 258 (81.4%). Recovery with no neurologic deficit, 267 (84.2%); focal neurologic deficit, 30 (9.5%); depressed mentation, 10 (3.2%); and death, 10 (3.2%), were documented. Signs of increased intracranial pressure (ICP) at admission [AOR: 1.415 (95% CI: 1.4058–9.557)], severe TBI [AOR: 2.553 (95% CI: 1.965–4.524)], presence of hyperglycemia [AOR: 2.318 (95% CI: 1.873–7.874)], and presence of contusion, diffuse axonal injury (DAI), or intracranial bleeding on the head computed tomography (CT) scan [AOR: 2.45 (95% CI: 1.811–7.952)] predicted poor TBI outcome. Conclusion. TBI contributed to 7.4% of pediatric ER visits. Pedestrian RTA and falls, early presentation (<24 hours of injury), and mild form of TBI among boys were the most common documented patterns. ICP, hyperglycemia, severe TBI, and presence of contusion, DAI, or intracranial bleeding on head CT predicted poor outcome. Strategies to ensure road safety and to prevent falls and animal-related injuries and TBI follow-up for ICP and glycemic controls are recommended.